Demand-driven evolution of IT-systems in healthcare - a case study for improving interdisciplinary processes - Lenz, Richard; Büsseker, Frank; Herlofsen, Herlof; Hinrichs, Frank; Zeiler, Thomas; Kuhn, Klaus (Methods of Information in Medicine, 2005)
Objectives: To analyze and to optimize interdisciplinary clinical processes, to introduce an IT-supported model for demand-driven system evolution in healthcare, and to demonstrate the feasibility of the approach for a clinical example and to present an evaluation. Methods: System evolution and change management are viewed as two sides of the same coin, thus formal methods for process analysis and IT system evolution were embedded into a goal-oriented change management model. Based on a process model, a Failure Mode and Effects Analysis (FMEA) and a computer simulation were performed. A tool for rapid application development (RAD) was used to incrementally improve the healthcare information system according to newly arising needs. Results: Each of the formal methods used contributed to the successful reorganization of the interdisciplinary clinical process. An evaluation demonstrated significant improvements. An integrated IT application was implemented to support the optimized process. Conclusions: Process improvement is feasible and effective when formal methods for process analysis and requirements specification are used in a reasonable and goal-oriented way. It might be necessary to trade off costs and benefits or simplify a given method in the context of a particular project. As the same information is utilized in different tools, it is supposed that the efforts for process analysis, documentation and implementation of adapted applications could be reduced if different tools were integrated and based on a single coherent reference model for description of clinical processes. © 2005 Schattauer GmbH.
UnivIS-Import:2015-03-09:Pub.2005.tech.IMMD.IMMD6.demand
Keywords: Computer simulation; FMEA; Information systems; Organizational innovation